Prevalence and characteristics of foreign body-induced upper gastrointestinal obstruction in dogs. - Laiket, Lalita; Sutthiprapa, Wijit; Khattiya, Suchawalee; Temwichitr, Pimjai; Rattanasrisomporn, Jatuporn; Thengchaisri, Naris (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: This study aimed to identify, categorize, and compare gastrointestinal foreign bodies in dogs, with a particular focus on those causing obstruction. The study also sought to distinguish between foreign body occurrences in the esophagus and the stomach, including the types of materials such as bones, plastic bags, fruit seeds, stones, and wires. Methods: A retrospective study was conducted on 261 dogs (151 males and 110 females) with foreign bodies lodged in the esophagus (n = 111) or stomach (n = 150). The sample consisted of 188 small dogs (24 kg). Results: The study’s findings indicate a higher prevalence of gastric foreign bodies (57.47%) compared to esophageal foreign bodies (42.53%). Small breeds dominated esophageal cases (92.79%), with only a small percentage being medium breeds (7.21%). In contrast, gastric cases included a high number of small breeds (56.67%), as well as significant percentages of medium (22.00%) and large breeds (21.33%). Small-breed dogs were more likely to have foreign bodies in the esophagus, while larger dogs (medium and large breeds) were more likely to have them in the stomach (p < 0.001). Distinct material patterns emerged between the esophagus and stomach. Notably, the esophagus showed a higher incidence of bones (61.26%) and dried dog snacks (23.42%) compared to the stomach (2.67% and 0.00%, respectively). Conversely, the stomach exhibited a higher incidence of fabrics (20.00% vs. 1.80%), plant materials (18.67% vs. 4.50%), metallic objects (18.00% vs. 8.11%), rocks (12.67% vs. 0.9%), rubber materials (10.67% vs. 0.00%), plastic materials (6.67% vs. 0.00%), and hairballs (2.67% vs. 0.00%), respectively. A temporal analysis revealed that within the esophagus, 28.83% of cases underwent foreign body removal within 24 h, 56.76% within 2–7 days, and 14.41% after more than 7 days. For foreign bodies within the stomach, removal occurred in 23.33% of cases within 24 h, 30.00% within 2 to 7 days, 22.00% after more than 7 days, and 24.67% at an unknown timing. A total of 111 cases involved foreign bodies lodged in the esophagus, and 150 cases involved items stuck in the stomach. Endoscopic methods were primarily employed to remove foreign bodies, with surgical intervention required for 4 (3.60%) esophageal and 8 (5.30%) gastric cases, including noncrushable bones and resistant items such as rubber ducks. In dogs with complete follow-up, surgical removal of esophageal foreign bodies had a higher mortality rate (3/4, 75.00%) compared with endoscopic removal (3/56, 5.36%) (p < 0.002), while no mortality was observed in dogs with gastric foreign bodies undergoing surgical or endoscopic removal (p = 0.149). Conclusion: Esophageal foreign bodies were primarily composed of bones and dried dog snacks, while gastric foreign bodies more often contained fabrics, plant materials, and metallic objects. These composition differences highlight the need for site-specific management strategies. J. Adv. Vet. Anim. Res., 12(2): 601–609, June 2025 http://doi.org/10.5455/javar.2025.l924